2018
DOI: 10.1051/e3sconf/20187404005
|View full text |Cite
|
Sign up to set email alerts
|

Towards a sustainable local business community by women℉s empowerment programs through corporate social responsibility (CSR)

Abstract: Based on data from Central Bureau of Statistics, the population of Indonesia in 2016 amounted to 258.71 million people, consisting of 128.72 million women and 129.99 million men. Thus, women need to be empowered to increase their competence so that they can contribute in the national economy. The aim of this paper is to analyze the impact of women's empowerment into a sustainable local business community through Corporate Social Responsibility (CSR). The qualitative research methodology was conducted in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Also, the results concur with Swastawati et al (2020) on their conclusion from an evaluation study on the performance of fishery-processing empowerment programme in Indonesia that execution and utilization of empowerment programmes (training and worksite technologies) can lead to increase in the production capacity and performance of the recipients. Similar results are established by Hidayati et al (2018) in a study on the impact of women's empowerment through corporate social responsibility programmes in Indonesia that empowerment programmes impacts positively to Vol 8 Issue 7 DOI No. : 10.24940/theijbm/2020/v8/i7/BM2007-065 July, 2020…”
Section: Correlation Of Capacity Building (Provision Of Workite Trasupporting
confidence: 82%
“…Also, the results concur with Swastawati et al (2020) on their conclusion from an evaluation study on the performance of fishery-processing empowerment programme in Indonesia that execution and utilization of empowerment programmes (training and worksite technologies) can lead to increase in the production capacity and performance of the recipients. Similar results are established by Hidayati et al (2018) in a study on the impact of women's empowerment through corporate social responsibility programmes in Indonesia that empowerment programmes impacts positively to Vol 8 Issue 7 DOI No. : 10.24940/theijbm/2020/v8/i7/BM2007-065 July, 2020…”
Section: Correlation Of Capacity Building (Provision Of Workite Trasupporting
confidence: 82%
“…These programs that teach skills don't only help women by themselves, but they also benefit the whole community. Kapoor (2019), Hidayati et al (2018) and Olabisi (2015). They found that helping women learn skills can make their local areas stronger financially, improve business, and give back to the community efforts or social duty known as corporate responsibility 'social jobless' through entrepreneurship, which creates jobs, too.…”
Section: Economic and Social Impacts Of Skill Developmentmentioning
confidence: 99%